The Palgrave Macmillan dictionary of diplomacy G.R. Berridge, Lorna Lloyd ; editorial consultants, Brian Barder, Laurence E. Pope, and Kishan S. Rana - Berridge, G.R (Palgrave Macmillan, 2012)
Indispensable for students of diplomacy and junior members of diplomatic services, this dictionary not only covers diplomacy's jargon but also includes entries on legal terms, political events, international organizations, e-Diplomacy, and major figures who have occupied the diplomatic scene or have written about it over the last half millennium.